2017
DOI: 10.1002/jbmr.3110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of 24 Patients With Rebound‐Associated Vertebral Fractures After Denosumab Discontinuation: Systematic Review and Additional Cases

Abstract: We aimed to study the clinical and imaging characteristics of patients sustaining vertebral fractures after denosumab discontinuation. For this purpose, we conducted a computerized advanced literature search that identified 13 published cases, and we additionally included another 11 new cases from our centers. Twenty-four postmenopausal women with vertebral fracture(s) after denosumab discontinuation, experiencing 112 fractures in total, were analyzed. The mean number of fractures per patient was 4.7. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 290 publications
(201 citation statements)
references
References 13 publications
7
179
2
6
Order By: Relevance
“…Before study start, reports indicated loss of gained BMD and a rebound effect on biochemical markers of bone metabolism in postmenopausal women with osteopenia or osteoporosis 12 months after discontinuation of a 24‐month treatment with denosumab . After the start of the present study, several case reports and post hoc analyses of the extension of the randomized controlled Freedom study reported increased incidences of vertebral fractures after discontinuation of treatment with denosumab, especially in patients with prevalent vertebral fractures . The growing awareness of this rebound effect and the incidence of vertebral fractures have led to reviews of the literature and position statements from the European Calcified Tissue Society and the European Menopause and Andropause Society regarding the potentially negative effect on bone health after discontinuation of denosumab treatment .…”
Section: Discussionmentioning
confidence: 75%
“…Before study start, reports indicated loss of gained BMD and a rebound effect on biochemical markers of bone metabolism in postmenopausal women with osteopenia or osteoporosis 12 months after discontinuation of a 24‐month treatment with denosumab . After the start of the present study, several case reports and post hoc analyses of the extension of the randomized controlled Freedom study reported increased incidences of vertebral fractures after discontinuation of treatment with denosumab, especially in patients with prevalent vertebral fractures . The growing awareness of this rebound effect and the incidence of vertebral fractures have led to reviews of the literature and position statements from the European Calcified Tissue Society and the European Menopause and Andropause Society regarding the potentially negative effect on bone health after discontinuation of denosumab treatment .…”
Section: Discussionmentioning
confidence: 75%
“…There was no relationship between the number of Dmab injections and LS‐BMD changes (month 12 to 24) in either group of women; in the Dmab group, the correlation coefficient ( rs ) between changes in LS‐BMD and number of denosumab injections (4 to 10) was −0.155 ( p = 0.415). In the ZOL group, the respective rs was −0.002 ( p = 0.991).…”
Section: Resultsmentioning
confidence: 89%
“…In the FREEDOM study and its Extension, Dmab was shown to increase BMD to such levels in a substantial number of women with postmenopausal osteoporosis that might lead in clinical practice to treatment discontinuation when the target is reached. However, the effect of Dmab, as of other antiosteoporotic medications with the exception of bisphosphonates, is rapidly reversible and may be also associated in a few patients with increased incidence of clinical vertebral fractures . A strategy to consolidate and maintain the Dmab‐induced BMD gains for longer periods of time is, therefore, desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which teriparatide exerts this extensive pro‐remodeling effect in patients is undefined but may relate to teriparatide stimulating a large pool of previously quiescent osteoclast precursors in a synchronized fashion. Given the recent suggestion that the accelerated bone remodeling which occurs when denosumab is discontinued (even in the absence of adding a pro‐remodeling drug) is associated with an increase risk of compound vertebral fractures, it seems prudent to suggest that physicians avoid prescribing this specific drug transition …”
Section: Introductionmentioning
confidence: 99%